Genetic basis of susceptibility to low‐dose paraquat and variation between the sexes in Drosophila melanogaster. Issue 9 (27th March 2021) - Lovejoy, Pamela C.; Foley, Kate E.; Conti, Melissa M.; Meadows, Samantha M.; Bishop, Christopher; Fiumera, Anthony C.
Abstract: Toxicant resistance is a complex trait, affected both by genetics and the environment. Like most complex traits, it can exhibit sexual dimorphism, yet sex is often overlooked as a factor in studies of toxicant resistance. Paraquat, one such toxicant, is a commonly used herbicide and is known to produce mitochondrial oxidative stress, decrease dopaminergic neurons and dopamine (DA) levels, and decrease motor ability. While the main effects of paraquat are well‐characterized, less is known about the naturally occurring variation in paraquat susceptibility. The purpose of this study was to map the genes contributing to low‐dose paraquat susceptibility in Drosophila melanogaster, and to determine if susceptibility differs between the sexes. One hundred of the Drosophila Genetic Reference Panel (DGRP) lines were scored for susceptibility via climbing ability and used in a genome‐wide association study (GWAS). Variation in seventeen genes in females and thirty‐five genes in males associated with paraquat susceptibility. Only two candidate genes overlapped between the sexes despite a significant positive correlation between male and female susceptibilities. Many associated polymorphisms had significant interactions with sex, with most having conditionally neutral effects. Conditional neutrality between the sexes probably stems from sex‐biased expression which may result from partial resolution of sexual conflict. Candidate genes were verified with RNAi knockdowns, gene expression analyses, and DA quantification. Several of these genes are novel associations with paraquat susceptibility. This research highlights the importance of assessing both sexes when studying toxicant susceptibility.